The accuracy of the axial length and axial length/corneal radius ratio for myopia assessment among Chinese children - Jingfeng Mu; Dan Zeng; Jingjie Fan; Meizhou Liu; Haoxi Zhong; Xinyi Shuai; Shaochong Zhang (Frontiers Media S.A., 2022)
ObjectivesThe aim of this study was to assess the association between axial length/corneal radius ratio (AL/CR ratio), AL, and refractive status and evaluate the accuracy of AL and AL/CR ratio for myopia assessment among Chinese children.MethodsA diagnostic trial was conducted in Shenzhen Eye Hospital from June 2020 to December 2020. Cycloplegic refraction and demographic characteristic survey were carried out, and AL and CR were measured. The Pearson correlation analysis between AL, AL/CR ratio, and spherical equivalent (SE) was carried out. The sensitivity, specificity, Youden index, positive predictive value, and negative predictive value of the AL/CR ratio and AL for myopia assessment were analyzed using cycloplegic refraction as the gold standard by drawing receiver operating characteristic (ROC) curves.ResultsA total of 300 children aged 8-18 years participated in this study. The Pearson correlation coefficient between AL and SE was −0.667 (P < 0.05) and −0.754 (P < 0.05) between AL/CR ratio and SE. There were significant differences in SE, AL, and AL/CR ratio among different age groups (p < 0.05). SE decreased by 1.185 diopter (D) for every 1 mm increase in AL and decreased by 0.667 D for every 0.1 increase in the AL/CR ratio. Taking cycloplegic refraction SE ≤ −0.50 D as the gold standard for the diagnosis of myopia, the area under the ROC curve of AL for myopia assessment was 0.836 (95% confidence interval [CI]: 0.767-0.906), with specificity, sensitivity, and Youden index of 0.833, 0.767, and 0.600, respectively. The area under the ROC curve of AL/CR ratio for myopia assessment was 0.937 (95% CI: 0.878-0.996), with specificity, sensitivity, Youden index, positive predictive value, and negative predictive value of 0.703, 0.913, 0.622, 0.956, and 0.771, respectively. The area under the ROC curve of the combination of AL/CR ratio and parental myopia for myopia assessment was 0.976 (95% CI: 0.957-0.996).ConclusionThe correlation between SE and AL/CR ratio was stronger than that between SE and AL in children. The AL/CR ratio may be an alternative indicator for myopia assessment in children, and the combination of demographic factors and AL/CR ratio can improve the accuracy of myopia assessment.